A heuristic to generate input sequence for simulated annealing to solve VRP. (6th August 2010) - Dhanalakshmi, R.; Parthiban, P.; Ghatak, Anirban
This paper addresses the issue of input sequence, which affects the results of simulated annealing (SA) for vehicle routing problem (VRP). Also, a heuristic has been proposed which improves the result by 1.7% than the well known and frequently used input sequence. With its ability to provide solutions of good quality at low computing times, the proposed heuristic has ample scope for application as an automated scheduler when implemented at the site of a logistics-planning cell.